Role of Word of Mouth Communication in North Cyprus: Painkillers and Dermocosmetics Products - Akgül, Çağlar Çağlar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
There are numerous companies in the global market who are in the same sector and competing with each other; they are offering almost similar products or services while they are reaching their customers. In the medical sector it is clearly considered that companies are producing too many medicines and derma-cosmetic products on the market and they are offering similar features and benefit products for their patients. The aim of this research is to contribute to the literature about Word of Mouth (WOM), which has a great impact in the medical sector especially in developing countries. As TRNC is a small semi-island, people rely more on word of mouth communication than any other promotional mixed elements. Thus, this research explores “The Importance of Word Of Mouth (WOM) Communication in the Medical Sector in the TRNC Market”. Therefore in this research Interpersonal Communication, Word of Mouth Communication and diffusion on innovation theory was used. In this study, quantitative research, survey method was conducted as primary resources and it was limited only to the painkiller and derma-cosmetic products in Famagusta TRNC market. Before collecting the accurate data 50 questionnaires were distributed as a pilot test and according to the feedback the pilot test questionnaire was renewed. Data collection was done by 320 respondents in 15 different areas in Famagusta. There were 33 questions in the questionnaire and it was prepared as in-house to explore the study. According to research it seen that people who live in Famagusta 110 of the respondents (34.4%) are doing periodic check-up. Also the 212 of the respondents (66.3%) take care for their personal care. In addition to this when they have some headache 101 (31.6%) of claimed that they directly gets painkiller medicine. Also 148 of the respondents claimed that they use derma-cosmetic products when they need it and when they pass purchasing process quality is the first criteria that they look for then price and brand names comes next. On the other hand only 36 of the respondents claimed that they get influenced form advertising. Lastly 241 of the respondents claimed that no matter either positive or negative experience they share this information with their close group and use either positive or negative WOM communication. Keywords: Word of Mouth (WOM), Derma-cosmetics products, Painkiller products.

ÖZ: Günümüzde küresel pazar alanında bir çok benzer ürünler farklı firmalar tarafından üretilmektedir. Bu benzer özellikteki ürün veya hizmetleri müşterilere sunarlar. Sağlık sektöründe bulunan firmalar çok fazla benzer özellikte medical ve dermo kozmetik ürünler üretip satmaktadırlar. Bu araştırmanın amacı, ağızdan ağıza iletişimin sağlık sektöründeki etkilerini göstermeye çalışmaktır. Kuzey Kıbrıs Türk Cumhuriyeti küçük bir yarım ada’dır. Dolasıyla insanlar yapılan promosyonlardan çok ağızdan ağıza yapılan iletişime güvenmektedir. Bu araştırma ile KKTC sağlık sektörü pazarında ağzıdan ağıza iletişimin önemi açıklanmaktadır. Ayrıca bu araştırmada Ağızdan ağıza iletişim ve kişiler arası iletişim teorileri kullanılmıştır. Bu araştırmada nitel araştırma anket teknikleri birincil kaynak olarak kullanıldı ve KKTC Gazimağusa sağlık sektöründeki ağrı kesici ve dermo kozmetik ürünler ile sınırlandırıldı. İlk olarak 50 farklı kişiye pilot anket uygulandı. Alınan bu bilgiler ışığında anket soruları geliştirlip son haline getirildi. Gazimağusa bölgesinde bulunan 15 ayrı yerden toplamda 320 kişi ile anket çalışması yapıldı. Bu araştırmayı yapmak için kişilere 33 farklı soru hazırlandı. Bu araştırmaya gore Gazimağusa’da yaşayan 110 kişiden (%34,4) katılımcı yıllık rutin checkup yapar. Ayrıca 212 kişiden (%66,3) katılımcı kişisel bakımına önem verir. 101 katılımcı (%31,6) baş ağrısı his ettiğinde direk olarak ağrı kesici alırlar. 148 katılımcı derma kosmetik ürünü ihtiyaç duyduğunda kullanır ve kaliteye önem verirler fakat diğer 36 katılımcı reklamlardan etkilenirler. Son olarak 241 katılımcı ise olumlu ve olumsuz deneyimlerini diğer çevrelerindeki kişiler ile paylaşırlar. Anahtar Kelimeler: Ağızdan Ağıza İletişim, Dermo kozmetik ürünler, Ağrı kesici ürünler.
Master of Arts in Communication and Media Studies. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2015. Supervisor: Assist. Prof. Dr. Anıl Kemal Kaya.
Keywords: Communication and Media Studies; Communication in marketing - Medical Secto - Cyprus, North; Oral communication - Public Opinion; Word - of - mouth advertising; Word of Mouth (WOM); Derma-cosmetics products; Painkiller products